Magyar László és a természettudományok: A 200 éve született magyar Afrika utazó és felfedező emlékére - Biernaczky, Szilárd (Afrika Tanulmányok / Hungarian Journal of African Studies, 2020)
Not long ago we were celebrating the 200th anniversary of one of the most known Hungarian Africanist László Magyar’s birthday. This paper seeks to offer on overview of many of Magyar’s observations in different fields of the natural sciences, which so far has not yet been discussed in details. Looking into his legacy, we can reveal many of his talents and knowledge in map-making, geography, agriculture, or demography, which may provide further ideas for more scientific research.